Methodological issues in visible LED therapy dermatological research and reporting - David Robert Grimes (PLoS ONE, 2025)
Background The advent of mass-market Light Emitting Diodes (LEDs) has seen considerable interest in potential dermatological applications of LED light photobiomodulation (PBM) for a range of conditions, with a thriving market for direct-to-consumer LED treatments, including red light, blue light, and yellow light wavelengths. Evidence of efficacy is however mixed, and studies report a wide range of irradiances and wavelengths as well as outcome measures, rendering interpretation, comparison, and even efficacy evaluation prohibitive and impeding evidence synthesis. Methods This work establishes a model for comparing patient received doses, applying this to existent studies to ascertain potential inhomogeneity in reported doses and wavelengths employed. Patient doses were contrasted to equivalent solar exposure time needed to achieve fluences reported at specified wavelengths in the red light (RL), blue light (BL), and yellow light (YL) portion of the spectrum, yielding a comparison of reported doses to typical solar irradiance at the Earth’s surface. Methodological aspects including dose validation, blinding, and bias were also analysed. Results 27 relevant studies for dermatological conditions including acne vulgaris (n=9, 33.3%), wrinkle-reduction (n=5, 18.5%), wound-healing (n=3, 11.1%), psoriasis severity (n=3, 11.1%), and erythemal index (n=7, 25.9%) were assessed. Outcome measures were highly heterogeneous between studies, with total patients ranging from 14 – 105 (median: 26). Fluences and wavelengths used in treatment differed over three orders of magnitude across studies even for the same conditions (0.1 J cm−2−126 J cm−2, median: 40.5 J cm−2). Derived equivalent solar time ranged from 0.01-19.35 hours (median: 3.3 hours), with central wavelengths between 405nm (BL) - 660nm (RL). No studies reported any dose validation, 10 (37.0%) were sponsored by the device manufacturer with a further 3 (11.1%) conducted by commercial dermatology practices offering the therapy under investigation. Assessors were unblinded to the treatment/ control groups in 33.3% (n=9), while a further 9 (33.3%) did not have any non-light control group, leaving only 33.3% (n=9) with both control group and blinded outcome assessment. Conclusions Results of this analysis suggest that fluences, wavelengths, and effective dose vary inconsistently between studies with often scant biological justification. This analysis suggests that better dose quantification and understanding of the underlying biophysics as well as plausible biological justifications for various wavelengths and fluences are imperative if LED therapy studies for dermatology are to be informative and research replicability improved.